2023
DOI: 10.3390/su15054264
|View full text |Cite
|
Sign up to set email alerts
|

Yoga, an Appurtenant Method to Improve the Sports Performance of Elite Romanian Athletes

Abstract: Yoga is a very popular trendy sport all over the world. Since its establishment and promotion, yoga has mostly been practiced in social clubs and studios, often being performed during optional courses in colleges. Basic yoga instruction is generally absent in middle schools. This study investigated and assessed the viability of integrating yoga practice into the sports training program of elite Romanian athletes. The research methods used include documentation and data collection via an online survey in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…They equated yoga with a basic and therapeutic preventative measure and an Asian school of thinking and philosophy that seeks to harmonize body, mind, and spirit. Other authors found the same results ( Lau et al, 2015 ; Subhra et al, 2021 ; Jangam et al, 2022 ; Bucea-Manea-Țoniș et al, 2023 ).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…They equated yoga with a basic and therapeutic preventative measure and an Asian school of thinking and philosophy that seeks to harmonize body, mind, and spirit. Other authors found the same results ( Lau et al, 2015 ; Subhra et al, 2021 ; Jangam et al, 2022 ; Bucea-Manea-Țoniș et al, 2023 ).…”
Section: Discussionsupporting
confidence: 63%
“…According to several researchers, practicing yoga for 4 weeks led to a substantial decrease in weight loss and a rise in the experimental group’s leg and back strength. In a study of handball players conducted by Godara et al, it was discovered yoga practice significantly boosted the players’ back strength ( Subhra et al, 2021 ; Bucea-Manea-Țoniș et al, 2023 ). A significant increase in the strength of the legs was observed in the research with a structured training program that included yoga teaching saw a substantial improvement in following the intervention agility and flexibility assessments as well as a dramatic improvement in balance after intragroup therapy ( Kim et al, 2015 ; Donald et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yoga has been extensively documented to offer a wide range of benefits, encompassing notable improvement in mental and physical health, reduced stress levels and overall improvement in QOL [ 21 ]. With the flight-or-fight stress reaction being interrupted by yoga practice, a condition physiologically opposed to that of the stress response can be attained, leading to a sense of harmony and connection between the mind and body [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These games hold cultural significance and are deeply rooted in the history and identity of the indigenous people. They often involve physical strength, agility, and teamwork, and are played for various purposes such as building community bonds, honouring ancestors, and promoting physical and mental well-being [67]. Moreover, indigenous games serve as a means of preserving and transmitting cultural knowledge and traditions from one generation to another [66].…”
Section: Indigenous Knowledge and Practices: Taxonomy Of Indigenous G...mentioning
confidence: 99%
“…Studies indicate that through participating in these games, indigenous communities can reinforce their cultural identity and strengthen their sense of belonging [66]. Furthermore, these games provide an opportunity for intergenerational interaction, fostering a sense of unity and solidarity among community members [67]. Remarkably, the elders pass down their knowledge and skills to the younger generation, ensuring the preservation of their heritage [67].…”
Section: Indigenous Knowledge and Practices: Taxonomy Of Indigenous G...mentioning
confidence: 99%